Environmental Business Law and Micro, Small, and Medium Enterprises (MSMEs): Legal Challenges and Pathways toward Sustainable Development - Nurbit, Nurbit; Wulandari, Desi; Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in national and global economies by contributing to employment creation, income distribution, and local economic development. However, MSME activities may also generate environmental impacts, particularly related to waste management, resource use, and pollution. Environmental business law serves as a critical legal instrument to regulate, guide, and control business activities to ensure environmental protection and sustainable development. This article examines the role of environmental business law in governing MSME activities, identifies key challenges in the implementation of environmental regulations for MSMEs, and proposes strategies to strengthen legal compliance while supporting economic sustainability. Using a normative legal research method supported by a literature review of international journals, this study finds that although environmental legal frameworks are increasingly comprehensive, MSMEs face structural and institutional constraints in compliance. Therefore, adaptive, educative, and inclusive legal approaches are essential to promote environmentally responsible MSMEs without undermining their economic viability.